KAJIAN INTEGRASI MODA ANGKUTAN UMUM DI KOTA BARU MAJA UNTUK MENINGKATKAN PELAYANAN BAGI KEBUTUHAN MOBILITAS MASYARAKAT - Heru Widodo; Salsabila Quratuain (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
The integration of public transport has become an essential element in the development of a sustainable transport system. The increase in the use of private vehicles is due to the fact that people have no better options on public transportation. Public transport must be reliable in order to be chosen by the community where one of the criteria of reliability is with services that can reach the travel demand implemented one in the provision of integrated transportation and in this case developed in the Maja New Town. This research was carried out with the method of evaluation of suitability of the function of Maja as an Independent City which is studied with patterns and potential of elevation and attraction to provide input from the passenger travel demand as well as the pattern of movement of passengers in Maja New Town. From the results of the research conducted obtained the fact that Maja is not entirely a New Independent Town but rather a satellite city to serve the needs of settlements for the activities in the area of Jakarta, Tangerang and its surroundings, this is seen from the pattern of traffic of passenger traffic quite large in the movement corridors of Maja – Tangerang – Jakarta served by KRL Jabodetabek Commuter Train. From the public transport service side and in the context of the integration of public transportation, in the Maja New Town this need to be developed transportation feeder for the needs of commuter movement that connects between the station center in the area of the settlement with the station node. Besides, it is necessary to provide public transport that serves the internal area that is also integrated with other node namely Train Station and Bus Terminal with reliable public transportation integration facilities